PENGARUH INVESTASI DAN PENGANGGURAN TERHADAP PERTUMBUHAN EKONOMI DAN KEMISKINAN DI PROVINSI BALI - Adi Sanjaya, Bagus Krisna (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 8 No 9 (2019): Vol. 8, No.9, September 2019, pp (1947-2194), 2019)
The purpose of this study was to determine the effect of investment and unemployment on economic growth and poverty in the Province of Bali. The population in this study were residents of Bali Province. The data collection method used in this study is a method of non-participant observation. The data analysis technique used is path analysis technique. The results of the study indicate that investment has a positive and significant effect on economic growth. Unemployment directly has no effect on economic growth. Investment has a negative and significant effect on poverty. Unemployment has a positive and significant effect on poverty. Economic growth has a negative and significant effect on poverty. Economic growth is unable to mediate the effect of investment on poverty. Economic growth is unable to mediate the effect of unemployment on poverty. Investment must be increased so that it can encourage high and quality economic growth so that it can be reached by the poor, so that poverty can decline and efforts need to be made to encourage proportional investment increases.